Avaliação da trajetória da Lei de Cotas na Universidade Federal do Ceará como política inclusiva sob a perspectiva dos egressos dos cursos de Farmácia, Odontologia e Enfermagem - Silva, Cíntia Paula Ribeiro da (2024)
Higher Education in Brazil has historically reflected a selective and exclusionary landscape. With the enactment of Law No. 12.711/2012, known as the Quota Law, a challenging opportunity arose to restructure public higher education, aiming to ensure its democratic nature by reserving spots for students from public schools, as well as Black, Brown, Indigenous students, and individuals with disabilities in federal universities and federal technical education institutions. Thus, the general objective of this research was to evaluate the trajectory of the Quota Law as an instrument for democratizing access to higher education and promoting social inclusion in the Pharmacy, Dentistry, and Nursing programs at UFC. To this end, its implementation and trajectory at UFC were examined, along with the complementary measures adopted for its application, such as the University Assistance Policy and the hetero-identification procedure. Additionally, the advances, challenges, and social transformations resulting from the law were investigated from the perspective of graduates from the aforementioned health-related courses, which, it is worth mentioning, are daytime programs that require both time and financial resources. The study’s temporal scope spanned from 2013, the date of its implementation, to 2023. Therefore, the study aimed not only to describe the law’s implementation but also to analyze its social and educational effects, seeking to understand, from the graduates’ perspective, the extent to which affirmative action quotas are effectively promoting transformation, inclusion, and the creation of a new social reality (Piovesan, 2008; Gomes, 2003). It also sought to identify aspects that could be improved to ensure more effective inclusion. For this purpose, the principles of in-depth evaluation (Rodrigues, 2008, 2011) were applied, aiming for a detailed, extensive, and comprehensive understanding of the policy from the perspective of the subjects and their contexts (Lejano, 2012). In terms of approach, this was a concurrent mixed-methods study, aiming to provide a broader understanding of the policy through the integration of quantitative and qualitative methods (Schoonenboom & Johnson, 2017). Field research data were collected via a Google Forms survey, encompassing the central concepts of the study, and were processed and analyzed in complementary ways using the Iramuteq software and manual analysis for thematic categorization, in light of Bardin’s content analysis (2004). Through the analysis, the transformative and inclusive potential of the quotas was confirmed; however, there remains a need for improvement, particularly concerning retention policies and the hetero-identification procedure, to ensure the legitimacy and effectiveness of the policy.